Social variation in adults’ lexical availability in Las Palmas de Gran Canaria: quantitative analysis and comparative notes - Medina Peñate, Inmaculada (Círculo de Lingüística Aplicada a la Comunicación, 2023)
This work is a sociolinguistic study of the lexical availability of Las Palmas de Gran Canaria, based on a sample of 72 informants and obtained according to the criteria of the PRESEEA project. After detailing quantitative aspects such as word average, number of different words, cohesion index or productivity of centers of interest, the incidence of social variables (‘sex’, ‘age’, ‘level of education’ and ‘socio-economic level’) on the lexical availability of adult native speakers of Las Palmas de Gran Canaria is analysed. Thus, it is found that the factor ‘sex’ has less influence on the results, but age allows us to observe the progressive increase in lexical ability, which stabilises in adulthood and decreases in the third generation, always in correlation with the level of education. The level of education and socio-economic status were found to be the factors that had the greatest impact on the results, with a statistically significant positive correlation between the years of study and the number of words of each informant.